2004
DOI: 10.1002/path.1570
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of ACE2 protein, the functional receptor for SARS coronavirus. A first step in understanding SARS pathogenesis

Abstract: Severe acute respiratory syndrome (SARS) is an acute infectious disease that spreads mainly via the respiratory route. A distinct coronavirus (SARS-CoV) has been identified as the aetiological agent of SARS. Recently, a metallopeptidase named angiotensin-converting enzyme 2 (ACE2) has been identified as the functional receptor for SARS-CoV. Although ACE2 mRNA is known to be present in virtually all organs, its protein expression is largely unknown. Since identifying the possible route of infection has major im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

128
5,482
18
208

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,370 publications
(5,836 citation statements)
references
References 23 publications
128
5,482
18
208
Order By: Relevance
“…ACE2 expression pattern in human kidneys is similar to the one in mouse kidneys, 1,22,27 with primary localization in the proximal tubular epithelium. However, inconsistencies can be found in mouse glomerular ACE2 presence as described even by the same group.…”
Section: Controlsmentioning
confidence: 53%
“…ACE2 expression pattern in human kidneys is similar to the one in mouse kidneys, 1,22,27 with primary localization in the proximal tubular epithelium. However, inconsistencies can be found in mouse glomerular ACE2 presence as described even by the same group.…”
Section: Controlsmentioning
confidence: 53%
“…In the human lung, immunostaining found that ACE2 was localized to endothelial and smooth muscle cells of large and small blood vessels, as well as type I and II alveolar epithelial cells and bronchial epithelial cells (32,33). In addition to AngI and AngII, ACE2 was found to hydrolyze apelin-13, neurotensin-(1-11), dynorphin A-(1-13), β-casomorphin-(1-7), and ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ACE2 is highly expressed in the heart, kidneys, testes, and also in the lungs, in particular (18,19). Alterations in the level of AngII can be seen up to the expression level of ACE2 (20).…”
Section: Introductionmentioning
confidence: 99%